Translational Narratology: An Eclectic Conceptual Model for Studying Translated Narrative Texts - Abolfazl Horri (Critical Literary Studies)
This paper introduces ‘translational narratology’ (TN) as an eclectic conceptual model for studying translated narrative texts. As a source-based theory, TN investigates the status of three planes of the original narratology in translation: ‘story’, ‘text’, and ‘narration’. In fact, as an eclectic model, TN aims to set a theoretical foundation for both the original narrative texts and their corresponding texts in translation. However, the process for the original writer and the translator is a little bit different: the writer usually begins with the elements of the ‘story’ plane, and then comes to the elements of ‘narration’ and ‘text’ planes, simultaneously; the translator, as a reader, begins with the ‘text/narration’, and then comes to the ‘story’ plane. The former is bottom-up; the latter is top-down. The translator may have nothing to do with the ‘story’ plane; however, he/she may deal with this plane in the process of reading, understanding, and, preferably, translating. Some theorists postulate that the original narrative models have made no room for the presence of the translator as the main agent of the translated narrative fiction. This paper sets the theoretical scene for the translator’s discursive presence in the translated narrative texts.